Diurnal variation and repeatability of arterial stiffness and cardiac output measurements in the third trimester of uncomplicated pregnancy. Issue 12 (December 2017) - Osman, Mohamed W.; Leone, Francesca; Nath, Mintu; Khalil, Asma; Webb, David R.; Robinson, Thompson G.; Mousa, Hatem A.
Abstract : Aim: To investigate same day repeated measures and diurnal variation of arterial stiffness, cardiac output ( CO ), stroke volume (SV) and total peripheral resistance (TPR) during the third trimester of normal pregnancy. Methodology: Pulse wave velocity (PWV) and augmentation index (AIx) were recorded using the Arteriograph, while CO, SV and TPR were recorded using noninvasive cardiac output monitoring. The measurements were obtained in the third trimester of pregnancy from 21 healthy pregnant women at four time points (morning, afternoon, evening and midnight) over a 24-h period. Triplicate measurements of 67 women were obtained at 5-min intervals to assess repeatability between measurements within a patient. Results: Diurnal measurements of arterial stiffness for brachial AIx, aortic AIx and PWV were not statistically significantly different at any of the four time points. Estimated means (SD) for PWV at the four stated time points were 7.81 (2.05), 8.45 (1.68), 7.87 (1.74) and 7.64 m/s (1.15), respectively ( P = 0.267). Estimates for AIx at those time points were 10.22 (15.62), 4.44 (10.07), 6.49 (10.92) and 8.40% (8.16), respectively ( P = 0.295). Similarly, mean arterial pressure, SV, SV index and TPR did not show any evidence of diurnal variation. However, we observed that the mean CO, cardiac index ( CI ) and heart rate (HR) varied from morning to midnight; the mean CO, HR and CI increased significantly in the afternoon compared with the corresponding mean morning measurements in a similar fashion to HR. Mean (SD) CO estimates at the four stated time points were 5.90 (1.33), 6.38 (1.49), 6.18 (1.43) and 5.80 ml/min (1.19), respectively, ( P < 0.001), whereas mean CI estimates were 3.65 (0.58), 3.93 (0.68), 3.81 (0.65), and 3.57 (0.48), respectively, ( P < 0.001), and mean HR estimates were 95 (12), 98 (13), 95 (12) and 88 (12.98), respectively ( P < 0.001). Triplicate measurements of 61 women in our repeatability study showed moderate-to-high correlation between observations on the same woman for all Arteriograph and noninvasive cardiac output monitoring variables (estimates of intraclass correlation ranged from 0.49 to 0.91). Conclusion: With the exception of CO, CI and HR which showed a diurnal variation, measurements of most haemodynamic parameters did not change significantly from morning to midnight, suggesting there was no evidence of systematic differences in the mean values of these variables at these time points. Multiple consecutive noninvasive measurements of vascular stiffness, CO, SV and TPR were highly correlated confirming repeatability of measurements in the third trimester of uncomplicated pregnancy, so these haemodynamic measurements do not need to be undertaken at a specific time period of the day.